Developing a conceptual model of hotel’s employee turnover in the Klang Valley, Malaysia - Chaichi, Kamelia (2018)
Hospitality and tourism is a growing industry in Malaysia. The growth in the hospitality and tourism industry is the reason for the development of the hotel sector. A good understanding of the factors influencing employee turnover intention in the hotel sector is fundamental since turnover is costly and diminishes the organizational effectiveness. Turnover intention is the principal focus of this study as it is regarded as an important predictor of actual turnover behaviour. The present study adopts the Theory of Planned Behaviour (TPB) as an appropriate and efficient model in examining turnover intention and behaviour. Personality role has received increasing attention in recent studies. Hence, by adding personality traits (e.g. positive personality traits (PPT) and core self-evaluation (CSE)) into the TPB model, the current study tries to add value to the literature. The purpose of this study is to propose and investigate an integrative model of turnover intention, which aims to achieve the following objectives: (1) to test the relationship between TPB constructs (Attitude, subjective norm, and perceived behavioural control) and employee turnover intention, (2) to test and evaluate the effect of positive personalities (PPT and CSE) on employee attitude, and (3) to examine the moderating effect of commitment on the relationship between TPB construct and turnover intention. The measurement characteristics of antecedent variables, along with the outcome variables, are explored and justified in the methodology chapter. The data was obtained from employees of hotels in the area of Klang Valley in Malaysia.The quantitative method adopted by this research uses the SMART-PLS to measure the validity of the research model and to analyse the data of this study. Findings reveal that all TPB constructs are significantly correlated with turnover intention, all the positive personality factors except self-efficacy predicts employee attitude towards the hotels, and three components of commitment partially moderate the relationship between TPB construct and turnover intention in the hotels in Malaysia. This study has important implications for hotel managers and human resource managers in the hotel industry. A good understanding of the factors affecting the turnover intention of the employees and their positive attitude towards the hotels is expected to help in the development of strategies for managers to retain employees in the hotel organization.